Trajectories, bifurcations and hysteresis in the Argentine economic cycle: the economic policy of Sudden Stops - Pablo Schiaffi (Ибероамериканские тетради, 2023)
This paper analyzes the evolution of the Argentine gross domestic product between 1875-2010. It intends to analyze its trajectory over time according to the periods of greater or lesser economic integration that the country experienced. An explanation of the poor performance that occurs between 1970-2010 (second globalization) is presented and compared with the period 1885-1914 (first globalization). This paper presents a series of graphic arguments that will allow us to analyze the evolution of the Argentine gross product from 1885 to 2010. It is not intended to explain or investigate the specific causes or reasons for the prosperity or depression that Argentina experienced in each of its episodes. Instead, an attempt is made to present longterm stylized facts seeking to compare moments of opening versus those of a closed economy over which the country oscillated in order to analyze long-term growth and economic volatility.